Moyamoya syndrome in Schimke immuno-osseous dysplasia - Vujić Ana; Obradović Slobodan; Igrutinović Zoran; Protrka Zoran; Janković Marijana; Radovanović Marija; Stajić Nataša; Medović Raša; Janković Sveta (Vojnosanitetski Pregled, 2023)
Introduction. Schimke immuno-osseous dysplasia (SIOD) is a rare autosomal recessive multisystem disorder associated with biallelic mutations of the SMAR-CAL1 gene. Vascular central nervous system complications in the form of Moyamoya syndrome (MMS) have been reported as a comorbidity in nearly half of the patients clinically presenting with severe migraine-like headaches, transient ischemic attacks (TIA), and ischemic or hemorrhagic infarctions. We present an illustrative case of an infantile form of SIOD with MMS, with a review of the latest diagnostic possibilities, as well as current diagnostic and therapeutic dilemmas in managing SIOD. Case report. We present a female patient with the infantile form of SIOD. The proband was born small for gestational age in the 34th gestation week with characteristic dysmorphic features. Genetic testing found a biallelic, nonsense mutation c.2542G>T in the SMARCAL1 gene. The patient presented early with TIA, seizures, and recurrent ischemic strokes. Magnetic resonance imaging (MRI) confirmed the presence of progressive brain atrophy with bilateral occlusion/stenosis of middle cerebral artery and anterior cerebral artery and a smoke-like collateral vessel appearance consistent with the MMS. At the age of 5 years and 9 months, the patient developed a high fever and cough with unknown cause, with a low erythrocyte and white blood cell count during four weeks, with a poor therapeutic response to antibiotics, transfusion of red blood cells, and granulocyte growth factor. She later died. Conclusion. Patients with SIOD may present progressive cerebral vascular changes and clinical neurologic deterioration early in the course of the disease. In such patients, early diagnosis and preventive revascularization surgery are of paramount importance. In diagnosing MMS, MRI angiography can be an appropriate substitute for standard invasive cerebral angiography.